Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The current status of the servant leadership and its relationship with job satisfaction from the viewpoint of faculty members at the University of HailCo-Prof. Miesam Fawzi Motiar Al-Azam2. The reality of Saudi families’ support for distance education and the challenges they faced in times of disasters and crises “The Corona Virus Pandemic (COVID-19) as a Model”Prof. Wadha Habab Alotaibi3. The Degree to Which Intermediate First-Graders in Jamoum Governorate Saudi Arabia Have Basic Skills in MathematicsCo-Prof. Abdul Malik Misfer Al-Maliki, Mr. Othman Abdullah Al-Sulami4. The competencies of social and emotional learning and their relationship to future skills among mathematics teachers in North Sharqiyah Governorate, Sultanate of Oman from their point of viewDr. Ali Said Sulaiyam Al-Matari, Mrs. Shamsa Mohamed Rashid Al-Noumani5. Academic buoyancy among female students of Umm Al-Qura University, Al-Zahir BranchMrs. Tahany Amaanullah Qasim6. The effect of using language learning strategies in teaching Arabic on the development of Some language skills of primary school studentsProf. Mahmoud Helal Abdelkader7. The reality of employing the Internet of Things in the educational process from the point of view of faculty members in Saudi universitiesMrs. Sarah Fahad Alharbi , Prof. Eiad Abdul-Aziz Altaf
Keywords: Journal of Educational and Psychological Sciences